Effect of Retort Processing on the Nutritional Composition of Ready-To-Eat Chicken Pepes Sausage - Amir, Arni Fazlin; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2025)
Pepes is traditional Indonesia cuisine and it made from chicken mixed with spices and wrapped with banana leaves. Recently, ready-to-eat products such as sausage were popular in market because it offered convenience to consumers. Ready-to-eat chicken pepes sausage provide minimal preparation requirements, nutritious and make it a good option for quick snack and meal solution. The objective of this study was to formulate the chicken pepes sausage by incorporating two different plant-based protein and compare the nutritional composition of before and after retort was conducted toward chicken pepes sausage. Therefore, two formulations of chicken pepes sausage were formulate, which were: F1 (pea protein isolate) and F2 (soy protein isolate). The sausages undergo retort processing at 121 °C for 25 minutes. This study focuses on analyse of moisture, protein, fat, carbohydrate, crude fiber, ash and energy based on AOAC: moisture analyzer for moisture content, Kjeldahl for protein content, Soxhlet for fat content, Different method for carbohydrate content, crude fiber analysis for crude fiber content, dry ashing for ash content and Atwater system for energy. Results showed that the nutritional properties of chicken pepes sausage are significantly changed by retort processing which F1 (pea protein isolate) has protein (10.58±0.05%), carbohydrate (35.23±1.04%), and energy (213.06±3.93%) while F2 (soy protein isolate) has protein (10.88±0.02%), carbohydrate (31.41±0.48%), and energy (201.20±1.90%). Thus, it can conclude the retort processing can reduce some nutritional properties such as moisture, protein, fat, ash and crude fiber in chicken pepes sausage.